Hubungan Kadar Low Density Lipoprotein Dengan Gangguan Pendengaran Sensorineural - Nurfadhilah Amini Nasution; Muhammad Edy Syahputra Nasution; Siti Masliana Siregar; Des Suryani (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2020)
Abnormalities of lipid metabolism in hyperlipidemia are the cause of atherosclerotic plaque in the inner ear and cranial nerves VIII, which can cause sensorineural hearing loss. Based on previous research, this theory is still questionable. Objective: To determine the relationship of LDL levels with sensorineural hearing loss. Method: This study is an analytic study with a cross-sectional approach. The research sample was taken based on a categorical descriptive formula with a large sample of 38 people. The data obtained is the result of laboratory tests, physical examination of the ears, nose and throat and audiometry examination of pure tone. This research was conducted at Medan Haji General Hospital and Putri Hijau Hospital II Medan. The number of research subjects was determined using consecutive sampling techniques. Data were analyzed using chi square test statistics. Results: There was a significant correlation of LDL levels with sensorineural hearing loss with a value of p = 0.001. The highest age in this study was 50-60 years of age, the most sex was female, the highest degree of hearing loss was moderateConclusion: There is a significant relationship between LDL levels with sensorineural hearing loss. Keywords: Audiometry, Hearing Loss, Sensorineural Hearing Loss, Low Density Lipoprotein, Lipid Profile